The Co-Mentoring Project: Overview and Outcomes - Renée A. Zucchero (Park University, 2008)
The Co-mentoring Project matched developmental psychology students with older adult volunteers for an intergenerational learning experience. Students conducted a biopsychosocial life review to increase understanding of older adult development and continuity in lifespan development. Each student developed a summary paper containing the older adult's life history, a developmental analysis, and personal reflection. A project description, including the scholarship of teaching and learning, and an overview of its outcomes are presented. The project goal was accomplished; students positively evaluated learning outcomes and displayed a significant increase in knowledge about older adults and aging. Implications for college instructors are discussed.